EXPLORING HEALTHCARE-ASSOCIATED INFECTIONS: KNOWLEDGE, ATTITUDE, AND BEHAVIOR OF EMERGENCY NURSES WORKING IN BANDUNG, INDONESIA - Hudzaifah Al fatih; Wang Jing-Jy (Belitung Nursing Journal, 2016)
Background: Healthcare associated Infections (HAIs) is considered being the most serious patient safety issue in health care settings and nurses in Emergency Department (ED) face greater risk of exposure to infectious pathogens. Objective: The objectives of this study were to examine knowledge, attitude and behavior towards HAIs of Indonesian nurses working in ED and to examine the relationship among the above three variables. Method: A cross-sectional study with self-reported survey was conducted at four hospitals in Bandung, Indonesia. The Healthcare Associated Infections Survey consisting of four domains: demographic characteristics, knowledge, attitude and behavior related to HAIs was used. The participants of this study covered 115 nurses. Results: The mean of overall performance on the knowledge was good 21.23 ±5.173 (range 9-30) and 92.2% of them believed that guideline for HAIs control practice can reduced the risk of infections. The mean score for behavior when practicing infection control was 37.7±5.570 (26-50). Marital status and working hours per week, influenced nurses’ knowledge of HAIs (rs = 0.185, p = 0.048). Work experienced have negative correlation with attitude towards HAIs (rs = -0.196, p = 0.035). Furthermore, type of hospital and working hours per week have been associated with nurses’ behavior towards HAIs (r = 0.191, p = 0.04). There was no significant relationship between knowledge, attitude and behavior towards HAIs. Conclusion: Even though the majority of ED nurses in Indonesia believe that precautionary guidelines can reduce the risk of HAIs, this study has indicated that nurses’ behavior toward HAIs is still insufficient.